RFID TECHNOLOGY ADOPTION IN ONE CARD SYSTEM - Effendi, Prahara Lukito; Jaryono, Jaryono; Kumorohadi, Untung (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
In the last few decades, scholars and practitioners have increasingly tried to understand the factors that influence technology acceptance. This research are also analysis factors to affect acceptance new technology namely Radio Frequency Identification. A distinguishing of previous study is this research use theory that rarely used to a technology not yet known namely innovation diffusion theory. Where this theory explain 5 characteristic acceptance technology, but in this research only choose 2 characteristics are used as variable namely relative advantage and complexity. Besides this research analyze the moderation can affect acceptance namely by review from side self-personality accepter. Test results using Moderated Regression Analysis (MRA) showed significance between variable. Implication this research stated that In an effort to continuously improve the use intention of RFID technology. This can do by providing intensive information related to various advantages of the use of RFID technology to improve safety, comfort, effectiveness and efficiency of the service system, and need to consider the individual personality factors in the implementing process of RFID technology.